The multivalent passive immune-protective vaccines of egg yolk immunoglobulin Y derived from live or inactivated Pseudomonas anguilliseptica against aquaculture pathogens (P. anguilliseptica and Aeromonas veronii) in goldfish (Carassius auratus) - Cui, Pan; Chen, Jing; Ma, Ziye; Xiao, Huihui; Lu, Juan; Wang, Juan; Xu, Gaoxiao (Frontiers in Marine Science, 2025)
BackgroundEgg yolk immunoglobulin Y (IgY) can be produced on a large scale, with simple and economical preparation and no drug residue, making it promising for application in prophylactic multivalent passive immunization vaccines for aquaculture.MethodsIgY antibodies of live Pseudomonas anguilliseptica (L-PA-IgY) or inactivated P. anguilliseptica (I-PA-IgY) were prepared by immunizing laying hens. Carassius auratus individuals were passively immunized with the two types of IgY antibodies and then challenged with P. anguilliseptica and Aeromonas veronii to detect the immune protection rate. The kidneys were homogenized and coated on Luria–Bertani (LB) solid medium to assess their bacterial content. Additionally, a cell phagocytosis assay was conducted to detect leukocyte phagocytosis. C. auratus serum was obtained to evaluate the recognition of the two bacteria by enzyme-linked immunosorbent assay (ELISA), and the expression of antioxidant factors [superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px)]. Furthermore, real-time fluorescence-based quantitative PCR (qRT-PCR) was performed to assess the expression of inflammatory factors (IL-6, IL-8, TNF-α, and IL-1β) in the kidney and spleen. Moreover, histopathological analysis was used to assess the integrity of visceral tissue structure, and immunofluorescence analysis was employed to assess the expression of apoptosis factor (p53) and DNA damage factor (γH2A.X) in the kidney.ResultsThe results indicated that the IgY antibodies of L-PA-IgY or I-PA-IgY exhibited passive immune protection against P. anguilliseptica and A. veronii. The sera of C. auratus passively immunized with L-PA-IgY or I-PA-IgY could interact with the two bacteria. Additionally, in C. auratus, the two IgY antibodies enhanced the phagocytic activity of leukocytes, reduced bacterial content in the kidneys, and diminished the expression of inflammatory and antioxidant factors. Furthermore, the structures of the kidney, spleen, and intestinal tissues were intact, and the expression of p53 and γH2A.X decreased in the kidney.ConclusionL-PA-IgY and I-PA-IgY can resist multiple bacterial infections and have immunoprotective effects with no significant differences. Moreover, the inactivated P. anguilliseptica immunization in laying hens is in line with animal welfare standards, and I-PA-IgY can serve as an immunization strategy of a prophylactic multivalent passive vaccine to resist multiple bacterial infections in aquaculture.